TNM staging compared with a new clinicopathological model in predicting oral tongue squamous cell carcinoma survival. Issue 10 (13th January 2014) - Okuyemi, Oluwafunmilola T.; Piccirillo, Jay F.; Spitznagel, Edward
Abstract Background The purpose of this study was to investigate the prognostic impact of comorbidity and of demographic and pathological factors on oral tongue squamous cell carcinoma (SCC) survival, and to compare the prognostic performance of a new clinicopathological model against the routinely used TNM staging. Methods We conducted a retrospective study of demographic, clinical, and pathological information of 166 patients with oral tongue SCC. Cox regression was used for multivariate analysis, model building, and model discriminatory analysis. Results Comorbidity had the most significant impact on overall survival (OS; log‐rank test, chi‐square = 36.34; p < .0001). Comorbidity, tumor dimension >2 cm, and presence of extracapsular spread (ECS) or vascular invasion were independent predictors of survival. A clinicopathological model based on these 4 variables (chi‐square = 60.23; p < .0001) was better (c‐statistic = 0.736) at predicting survival compared to pathological TNM staging (c‐statistic = 0.645). Conclusion Comorbidity combined with tumor dimension, ECS, and vascular invasion provide a better prediction of oral tongue SCC survival than TNM staging alone. © 2014 Wiley Periodicals, Inc. Head Neck 36: 1481–1489, 2014